Experiences of Pregnancy Following Stillbirth: A Phenomenological Inquiry - Phelan, Lauren (Canadian Journal of Counselling and Psychotherapy, 2020)
The goal of this qualitative study was to help identify the experiences and needs surrounding a pregnancy that follows a stillbirth. Six cisgender women who had experienced a stillbirth within the past 1 to 5 years and who subsequently had given birth to a child or children that they were currently parenting were interviewed for this study. van Manen’s hermeneutical phenomenological method was used in the thematic analysis of the interview transcriptions, and six common themes emerged from the participants’ stories: (a) a sense of isolation, (b) an acute sense of anxiety and fear, (c) a sense of responsibility and guilt, (d) a sense of loss of control and helplessness, (e) an ongoing sense of connection to the child who was lost, and (f) a sense of transformation through loss. Implications for counselling practice, along with recommendations for future research, are discussed.